2019
DOI: 10.1002/jcc.26068
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Nature and Predicting Strength of Hydrogen Bonds: A Correlation Analysis Between Atoms‐in‐Molecules Descriptors, Binding Energies, and Energy Components of Symmetry‐Adapted Perturbation Theory

Abstract: This work studies the underlying nature of H‐bonds (HBs) of different types and strengths and tries to predict binding energies (BEs) based on the properties derived from wave function analysis. A total of 42 HB complexes constructed from 28 neutral and 14 charged monomers were considered. This set was designed to sample a wide range of HB strengths to obtain a complete view about HBs. BEs were derived with the accurate coupled cluster singles and doubles with perturbative triples correction (CCSD(T))(T) metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
570
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 936 publications
(597 citation statements)
references
References 62 publications
(117 reference statements)
26
570
1
Order By: Relevance
“…However, the values of the V local potential energy of the electrons at the critical point of the H‐bond, which is the most popular descriptor of H‐bond, were not presented in these papers by Rusinska‐Roszak. The V values were widely used for estimation of the H‐bond energy by means of the Espinosa's equation and its modified versions . For this reason, we had to calculate this parameter additionally.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the values of the V local potential energy of the electrons at the critical point of the H‐bond, which is the most popular descriptor of H‐bond, were not presented in these papers by Rusinska‐Roszak. The V values were widely used for estimation of the H‐bond energy by means of the Espinosa's equation and its modified versions . For this reason, we had to calculate this parameter additionally.…”
Section: Methodsmentioning
confidence: 99%
“…The V values were widely used for estimation of the H-bond energy by means of the Espinosa's equation [21][22][23][24][25][26] and its modified versions. [27][28][29][30][31] For this reason, we had to calculate this parameter additionally. Since earlier we obtained the dependence of the IMHB energy on the V descriptor using the B3LYP/6-311++G(d,p) protocol, [29] the additional calculations of some hydroxycarbonyl aliphatic compounds and β-diketones were performed with the B3LYP functional [32] and the 6-311++G(d,p) basis set.…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, one alternative consists of the use of the QTAIM topological parameters obtained through the Multiwfn. 32 In a very interesting contribution of Lu and collaborators, 35 a new classification for the intermolecular hydrogen bond was proposed, and on the basis of a correlation analysis, it was discussed that the ρ(r) at the bond critical point (BCP) could be employed for quick and reliable prediction of the bond energy (BE) associated with hydrogen bonds for neutral and charged complexes. The BEs associated with intermolecular and intramolecular hydrogen bonds in 7′ FcN 3 @β-CD were evaluated as proposed by Lu and collaborators (Table S4, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…According to Table S4, the BE for the intermolecular hydrogen bond formed by N2 and H68 corresponds to −5.43 kcal mol −1 , a hydrogen bond with strength classified in the range "weak to medium" (BE varying from −2.5 to −14.0 kcal mol −1 ) with electrostatics as major nature. 35 Finally, the application of such an approach to determine the BE for the intramolecular hydrogen bond belt in β-CD gives values varying from −4.50 to −5.62 kcal mol −1 (Table S4, Supporting information). Such values are coherent with the stability of the intramolecular hydrogen bond in β-CD.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The NCI index analysis is also revealed that hydrogen bonding is an important interaction between MTX–CPT monomers in both complexes. According to the NCI index analysis, the hydrogen bonding interactions are classified into strong (O─H···N and O─H···O), moderate (N─H···O), and weak (C─H···O and C─H···N) hydrogen bonds . However, two major differences between R‐ and N‐conjugate have been observed in terms of the binding affinities: (a) The interaction between MTX and CPT in R‐conjugate complex involves a T‐shaped π–π stacking (denoted by the black rectangle in Figure ) while in N‐conjugate complex, phenyl rings of MTX in both monomers are not attracted by π–π stacking interactions due to geometry consideration.…”
Section: Resultsmentioning
confidence: 99%